Paleoecology : past, present, and future - Bottjer, David J. (Chichester, West Sussex : Wiley, 2016)
Paleucology is a discipline that uses evidence from fossils to provide an understanding of ancient environments and the ecological history of life through geological time. This text covers the fundamental approaches that have provided the foundation for present paleucological understanding, and outlines new research areas in paleucology for managing future environmental and ecological change. Topics include the use of actualism in paleucology, development of paleucological models for paleunvironmental reconstruction, taphonomy and exceptional fossil preservation, evolutionary paleucology and ecological change through time, and conservation paleucology. Data from studies of invertebrates, vertebrates, plants and microfossils, with added emphasis on bioturbation and microbial sedimentary structures, are discussed. Examples from marine and terrestrial environments are covered, with a particular focus on periods of great ecological change, such as the Precambrian-Cambrian transition and intervals of mass extinction. Readership: This book is designed for advanced undergraduates and beginning graduate students in the earth and biological sciences, as well as researchers and applied scientists in a range of related disciplines.
Overview -- Deep time and actualism in paleoecological reconstruction -- Ecology, paleoecology, and evolutionary paleoecology -- Taphonomy -- Bioturbation and trace fossils -- Microbial structures -- Across the great divide: precambrian to phanerozoic paleoecology -- Phanerozoic level bottom marine environments -- Reefs, shell beds, cold seeps, and hydrothermal vents -- Pelagic ecosystems -- Terrestrial ecosystems -- Ecological change through time -- Ecological consequences of mass extinctions -- Conservation paleoecology.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Paleoecology; Ecology; Global environmental change; Ecology; Global environmental change; Paleoecology; NATURE / Animals / Dinosaurs & Prehistoric Creatures; NATURE / Fossils; SCIENCE / Paleontology; Electronic books